(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research mainly aims to identify the effect of the conflict between the independence of the auditor and the provision of advisory services to management in expressing an impartial opinion. The research method used in the current research was based on two basic approaches: the inductive approach aims to build a scientific framework for the dimensions of the research problem and its objectives, by relying on scientific books, articles, research, scientific seminars and published periodicals related to the research topic, and the deductive approach by designing a questionnaire list to collect data related to the scope of the research. And testing the research hypotheses by surveying the opinions of a sample of auditors in Baghdad. The target research population is all external audit offices operating in Baghdad Governorate, licensed and approved by the Iraqi Auditing and Oversight Profession Council, which number 150 offices and 20 companies that actually practice the auditing profession. The sample was selected using a simple random sampling method with a percentage of 40% of The size of the total population, as the sample size was 68 individuals from the auditors, and after distributing the questionnaire and retrieving it, the number of valid returned questionnaires reached 57 questionnaires, at a rate of 84%. The results of the statistical test of the research hypotheses indicated that there is a relationship between the provision of consulting services and the independence of the auditor on the one hand, and on the other hand there is a relationship between the provision of consulting services and the professional opinion of the auditor. It also indicated that the auditor’s impartial technical professional opinion is moderately affected by the implications of providing advisory services on the auditor’s independence. The researchers concluded a number of recommendations, the most important of which were: • The necessity of setting standards for consulting services that can be provided by audit offices and companies in Iraq. Issuing systems and standards concerned with providing advisory services in an appropriate and more accurate manner that guarantees the independence of the auditor throughout the assignment period. • The necessity of having departments in large and medium audit offices and companies that specialize in providing consulting services to their clients and that they be separate from those departments that provide audit services for financial statements.